ANALYSIS OF THE PRACTICE OF CORRUPTION IN ELECTRONIC PROCUREMENT SERVICE SYSTEM IN THE KEPULAUAN RIAU PROVINCE - Rendra Setyadiharja; Achmad Nurmandi; Suyito (Universitas Pancasakti Tegal, 2017)
ranging from conventional forms filled with indications of bribery and corrupt, now converted into a system of procurement of goods and services electronically with Electronic Procurement Service Systems (LPSE). Expectations the central government and local government is to minimize the occurrence of graft, a fictitious project, markup or transactional in the procurement of goods and services, but also LPSE system has never been separated from the threat of any indication of corruption in the procurement of goods and services. The purpose of this research is to know how corruption practices on the procurement of goods and services at Electronic Procurement Service in Kepulauan Riau Province. The method used was the exploratory qualitative approach. Data collection method used is by interview (indebt interview). Interviews were conducted with several informants, namely Kepulauan Riau Province Electronic Procurement Service (LPSE), Kepulauan Riau Province Procurement Service Unit (ULP), Kepulauan Riau Province Development Administration Bureau, and Provider of Goods and Services. The results of this research are descriptions of cases of corruption in the LPSE system in Kepulauan Riau Province, and the mode of operation corruption practices that occur in the LPSE system in Kepulauan Riau province.